Pembuktian Tidak Langsung Dalam Kasus Perjanjian Kartel Impor Bawang Putih; Analisis Putusan Ma No.1495 K/Pdt.Sus-Kppu/2017 - Imam Santoso; Muhammad Ali Hanafiah Selian (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study aims to analyze the application and strength of indirect evidence in the case of the agreement on the importation of garlic cartels conducted by the Supreme Court of the Republic of Indonesia in the decision Number 1945 K / Pdt.Sus-KPPU / 2017. The Supreme Court in its decision used indirect evidence. The research method uses a type of normative legal research with a normative juridical approach by reviewing the applicable legislation, doctrine or expert opinion, and the existing literature books. The results of this study explain that the application of the concept of indirect evidence is not appropriate, because indirect evidence is not explicitly mentioned explicitly in Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition.Keywords: Indirect Monopoly Evidence, Supreme Court